PENGARUH KOMUNIKASI GURU DALAM MENGAJAR TERHADAP EFEKTIVITAS PEMBELAJARAN (Penelitian di Madrasah Tsanawiyah Serba Bakti Suryalaya Kecamatan Pageurageung Kabupaten Tasikmalaya) - Ardiati, Syarifah Setiana; Suhrowardi; Ihsan Ahmad Fauzi (Journal Education and Government Wiyata, 2023)
Education is a process of transferring knowledge, values, and culture, throuugh educative communication between teachers and students. Teacher communication in teaching has implications for the effectiveness of learning. Ideally, if the teacher’s communication in teaching runs effectively, the success or effectiveness of learning will be high. Meanwhile if the teacher communication in teaching is less effective, the success or effectiveness of learning will be low. This description attracts the author’s interest to determine the effect of teacher communication in teaching on learning effectiveness. The research method that the author uses is a descriptive method with a quantitative appproach. Based on the result of data processing, teacher communication in teaching has a positive influence on the effectiveness of learning. This can be interpreted that the alternative hypothesis is accepted and in other words there is a positive and significant influence of teacher communication in teaching on the effectiveness of learning in class IX MTs Serba bakti suryalaya.